Insulin use and persistence in patients with type 2 diabetes adding mealtime insulin to a basal regimen: a retrospective database analysis - Bonafede, Machaon M (BioMed Central, 2011)
BACKGROUND: The objective of this study was to characterize insulin use and examine factors associated with persistence to mealtime insulin among patients with type 2 diabetes (T2D) on stable basal insulin therapy initiating mealtime insulin therapy. METHODS: Insulin use among patients with T2D initiating mealtime insulin was investigated using Thomson Reuters MarketScan(® )research databases from July 2001 through September 2006. The first mealtime insulin claim preceded by 6 months with 2 claims for basal insulin was used as the index event. A total of 21 months of continuous health plan enrollment was required. Patients were required to have a second mealtime insulin claim during the 12-month follow-up period. Persistence measure 1 defined non-persistence as the presence of a 90-day gap in mealtime insulin claims, effective the date of the last claim prior to the gap. Persistence measure 2 required 1 claim per quarter to be persistent. Risk factors for non-persistence were assessed using logistic regression. RESULTS: Patients initiating mealtime insulin (n = 4752; 51% male, mean age = 60.3 years) primarily used vial/syringe (87%) and insulin analogs (60%). Patients filled a median of 2, 3, and 4 mealtime insulin claims at 3, 6, and 12 months, respectively, with a median time of 76 days between refills. According to measure 1, persistence to mealtime insulin was 40.7%, 30.2%, and 19.1% at 3, 6, and 12 months, respectively. Results for measure 2 were considerably higher: 74.3%, 55.3%, and 42.2% of patients were persistent at 3, 6, and 12 months, respectively. Initiating mealtime insulin with human insulin was a risk factor for non-persistence by both measures (OR < 0.80, p < 0.01). Additional predictors of non-persistence at 12 months included elderly age, increased insulin copayment, mental health comorbidity, and polypharmacy (p < 0.05 for all). CONCLUSIONS: Mealtime insulin use and persistence were both considerably lower than expected, and were significantly lower for human insulin compared to analogs.